Manajemen Pengembangan Kurikulum Pendidikan Agama Islam - Ma’arif, Mohamad Ahyar (LP3M Universitas Islam Zainul Hasan Genggong, 2017)
Development in the field of education based on philosophy of the State, the values ​​of Humans and Religion, sustainability and educational goals of national and institutional directed to human form physically and mentally healthy, internalized faith and devotion, have knowledge and skills, able to develop creativity and responsibility, able to develop high intelligence with noble character, and love of the nation and people. To reach the expected educational goals, the curriculum in the field of Islamic education has a very urgent role that is expected to give effect to the development, growth and development of human beings.